The Effect of Price, Service Quality, and Product Quality on Customer Loy-alty with Customer Satisfaction as a Mediating Variable at Richeese Factory Muncul Branch: A Literature Study - Aji Muhamad Rivky; Edward S. Tampubolon; Annuridya Rosyidta P.O; Afina Putri Vindiana (Law and Economics, 2026)
Increasingly fierce competition in the fast food industry requires companies to understand the factors that influence customer satisfaction and loyalty. This study aims to analyze the effect of price, service quality, and product quality on customer loyalty, with customer satisfaction as a mediating variable at Richeese Factory Muncul Branch. This study uses a quantitative approach with a survey method through questionnaires. The analysis technique used is Structural Equation Modeling Partial Least Squares (SEM-PLS). The data was analyzed using the SmartPLS application. The results show that price, service quality, and product quality have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant effect on customer loyalty. Customer satisfaction is proven to act as a mediator in the effect of price, service quality, and product quality on customer loyalty. These findings emphasize the importance of customer satisfaction as a major factor in increasing customer loyalty in the fast food industry.